2009
DOI: 10.1074/jbc.m109.012443
|View full text |Cite
|
Sign up to set email alerts
|

Differential Enzymatic Activity of Common Haplotypic Versions of the Human Acidic Mammalian Chitinase Protein

Abstract: Mouse models have shown the importance of acidic mammalian chitinase activity in settings of chitin exposure and allergic inflammation. However, little is known regarding genetic regulation of AMCase enzymatic activity in human allergic diseases. Resequencing the AMCase gene exons we identified 8 non-synonymous single nucleotide polymorphisms including three novel variants (A290G, G296A, G339T) near the gene area coding for the enzyme active site, all in linkage disequilibrium. AMCase protein isoforms, encoded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
68
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 29 publications
9
68
1
Order By: Relevance
“…Consistently with previous reports, recombinant mouse AMCase had the highest activity at pH 2.0 (Boot et al 2001; Kashimura et al 2013), whereas the recombinant human AMCase was most active at around pH 4.0–5.0 (Chou et al 2006; Seibold et al 2009; Goedken et al 2011) with the human enzyme being significantly less active as compared with the mouse AMCase (fig. 1 C ; supplementary table S1_1 and S1_2, Supplementary Material online; P < 0.01).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Consistently with previous reports, recombinant mouse AMCase had the highest activity at pH 2.0 (Boot et al 2001; Kashimura et al 2013), whereas the recombinant human AMCase was most active at around pH 4.0–5.0 (Chou et al 2006; Seibold et al 2009; Goedken et al 2011) with the human enzyme being significantly less active as compared with the mouse AMCase (fig. 1 C ; supplementary table S1_1 and S1_2, Supplementary Material online; P < 0.01).…”
Section: Resultssupporting
confidence: 92%
“…Seibold et al (2009) described nonsynonymous SNPs (nsSNPs) that variably endowed isoforms of human AMCase with differential enzymatic activity and showed that a haplotype encoding an isoform of AMCase with heightened enzyme activity was associated with protection from asthma in humans. No detailed knowledge is available regarding genetic and evolutional regulation of chitinolytic activity of AMCase.…”
Section: Introductionmentioning
confidence: 99%
“…So far, we have observed a substantial increase in catalytic efficiency of MACase compared to AMCase. In our study, we compared MACase to a variant of human AMCase that is catalytically more active than the originally discovered version (AF290004) and is shown to be associated with protection from asthma (Seibold et al, 2009). It could be possible that macaques needed an even more active enzyme to efficiently remove chitin, and therefore prevent an allergic response (Reese et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…Our version of the gene was slightly different from the variant (accession number AF290004) described in the original publication (Boot et al, 2001). At the protein level it contained N45D, D47N and R61 M substitutions which are known genetic variations (Seibold et al, 2009). The crystal structure of our variant has been solved recently (Olland et al, 2009).…”
Section: Human Amcase Cloningmentioning
confidence: 97%
See 1 more Smart Citation